DEXTERITY OF ACCEPTING AND DECLINING ORAL INVITATIONS OF SMK STUDENTS IN SPEAKING PERFORMANCE - Sahan, Anselmus; Bulle, Hermelinda Azi; Lasi, Febronia (Premise: Journal of English Education and Applied Linguistics, 2023)
Accepting and declining invitations bridges the speakers and hearers involved in direct communication to get mutual understanding. In a classroom context, the knowledge of accepting and declining invitations is essential since both teachers and students should be able to create a dialogical relationship. Therefore, this study aims to determine whether the eleventh-year students of SMK Negeri Nibaaf, Kefamenanu, have mastered accepting and declining the invitation, describe their difficulties, and categorize their level of mastery. To describe the whole process, the researchers applied a quantitative method. To get the data, this study used an oral test given to eleven students learning English in the 2020/2021 school year. This study used mobile phones to record the oral test. Their performance was analyzed using the parts of accepting and declining an invitation and four aspects of speaking: fluency, vocabulary, grammar, and pronunciation. The result shows that their average score is 89.5. It indicates that their dexterity is categorized as very good, and their level of mastery is excellent. However, they made 109 (48%) right and 23 (8%) wrong answers. They also faced pronunciation difficulties (11 (or" 4%) right and 55 (or: 20%) wrong answers) and grammar20 (or: 7%) right and 46 (or: 17%) wrong answers). It implies that teaching speaking should pay more attention to accepting and declining an oral invitation.